Faktor dan Penjadualan Shift Kerja - Lientje Setyawati Maurits; Imam Djati Widodo (Teknoin, 2008)
Work shift has negative effect in physical and mental health, work performance and job accident. Disturbance of circadian rhythms is indicated as source of the problems. This  article  explores  some  researches  related  to  the  impacts  of  work  shift  and establishes basic principles of work shift scheduling that considers human need and limitation. Keywords: work shift, circadian rhythms, accident, fatique.